A NUMERICAL STUDY OF SUBSTANCE SPREAD IN THE POLL FROM TWO POINT SOURCES - Ashar, Nurcahya Yulian; Hariyanto, Susilo (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
Problems related to the purification of holding pool or reservoir become an interesting discussion in real events. In this paper, the author will modeling the distribution of the substance/purifier in a pool model with turbulent water flow using the diffusion-convection equation. The Dual Reciprocity Method is applied to the diffusion-convection equation whose derivation will be discussed in this paper. This method is chosen because the problem cannot be solved analytically, so it must be solved numerically. The Dual Reciprocity Method has good flexibility in problems of water infiltration, pollutant spread, and heat transfer. In this paper also discuss velocity profile of turbuelent flow from upcoming part of pool region. So before using DRM, will be used numerical solution of turbulent flow by k-epsilon turbulent model. In numerical calculations, two source points are selected whose positions are combined to see the most effective way to make the substance/purifier evenly distributed in the pool.